2023
DOI: 10.3390/ph16010117
|View full text |Cite
|
Sign up to set email alerts
|

Combined Gamma Conglutin and Lupanine Treatment Exhibits In Vivo an Enhanced Antidiabetic Effect by Modulating the Liver Gene Expression Profile

Abstract: Previous studies have individually shown the antidiabetic potential of gamma conglutin (Cγ) and lupanine from lupins. Until now, the influence of combining both compounds and the effective dose of the combination have not been assessed. Moreover, the resulting gene expression profile from this novel combination remains to be explored. Therefore, we aimed to evaluate different dose combinations of Cγ and lupanine by the oral glucose tolerance test (OGTT) to identify the higher antidiabetic effect on a T2D rat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…They have garnered significant attention from farmers and breeders due to their potent bitter taste and potential toxicity at high doses ( Pereira et al., 2022 ), which is why it is recommend they remain below the industry threshold of 0.02% ( Boschin et al., 2008 ). Nevertheless, recent studies show that lupanine, one of the prevalent alkaloids of the genus Lupinus in both their foliage and their seed ( Hill, 2003 ), has been shown to have anti-inflammatory and anti-cancer properties ( Guerra-Ávila et al., 2023 ). Sparteine, another lupin alkaloid, has been associated with antiarrhythmic and anticonvulsant properties ( Frick et al., 2017 ), showcasing the dual nature of alkaloids in legumes as both anti-nutritional factors and potential pharmaceutical agents.…”
Section: Legume Phytochemicals Their Biochemistry and Significancementioning
confidence: 99%
“…They have garnered significant attention from farmers and breeders due to their potent bitter taste and potential toxicity at high doses ( Pereira et al., 2022 ), which is why it is recommend they remain below the industry threshold of 0.02% ( Boschin et al., 2008 ). Nevertheless, recent studies show that lupanine, one of the prevalent alkaloids of the genus Lupinus in both their foliage and their seed ( Hill, 2003 ), has been shown to have anti-inflammatory and anti-cancer properties ( Guerra-Ávila et al., 2023 ). Sparteine, another lupin alkaloid, has been associated with antiarrhythmic and anticonvulsant properties ( Frick et al., 2017 ), showcasing the dual nature of alkaloids in legumes as both anti-nutritional factors and potential pharmaceutical agents.…”
Section: Legume Phytochemicals Their Biochemistry and Significancementioning
confidence: 99%
“…For HFD-induced mice (high-fat rations provided 5.1 kcal/g of energy, with protein, carbohydrate and fat accounting for 18, 22 and 60% of total dietary energy, respectively, inducing hyperglycemia and steatohepatitis), supplementation with 2 g/kg BW of lupine protein isolate for 3 weeks significantly decreased their blood glucose and improved insulin sensitivity via upregulating the hepatic Fasn gene and downregulating the Gys2 and Gsk3b genes [ 55 ]. In another study, a combination of γ-conglutin and lupanine was used to treat type 2 diabetic (T2D) rats (a rat model of spontaneous diabetes mellitus commonly used as an animal model for type II diabetes mellitus) [ 54 ]. The results of deoxyriboNucleic acid (DNA) microarray and bioinformatics analysis showed that the combination of 28 mg/kg BW γ-conglutin and 20 mg/kg BW lupanine significantly reduced blood glucose and lipid levels.…”
Section: Pulse Proteins and Their Hydrolysates For Improving Metsmentioning
confidence: 99%
“…To assess the distribution of the triplicates from all groups, principal component analysis (PCA) and hierarchical clustering, provided by TAC, were used. In the transcriptome analysis, the group sample signals of each gene were compared to all groups to identify which coding genes modify their expression in comparison to the healthy group as reported before [72], and how some genes are expressed oppositely between both diabetic groups. For functional enrichment analysis, STRING database (version 11.5) was used to analyze differentially expressed target interactions.…”
Section: Bioinformatic Analysismentioning
confidence: 99%